(3JeTjI GdEQTGOs - (3TQa GdOjf ESeGYjd Hf CHi HcQ GdebQi GdTGhQis; (3TQa GdOjf ESeGYjd Hf CHj HcQ Hf YHO Gddg Hf EHQGgje GdebQj GdTQLj GdMSjfj, GdTGhQj GdRHjOj Gdjefj,J (B837 (3g` s ((3eOjfI JYR s)
(3ChdgG (B:s
(3GdCTLGQ aEfG fbOQg HeNGda hSW , adG jbOQ Gddhf HGdMjR , hdG GdWYe HGdNd s
(3BNQgG (B:s
(3BNQg ef HGH GdRcGI (B:" (3hCeG eG jMGLg dfaSg adG jMQe , dcf Ef cGf eef jUHQ Ydi GdEVGaI agh eSJMH ai Mbg , hEdG aecQhg hGddg CYde Je GdfUa GdChd ef JeTjI GdEQTGO s
(3HgG fXGe GdJYbjHIs
(3Ydi GdfSNI JUMjM hHYV GdJbjjOGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3Gdabg GdTGaYjs